From life history theory to clinical practice: potential markers of fast life strategy - O. T. Kim; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Currently, there is increasing evidence that early human development mediates the risk of early cardiometabolic diseases and their risk factors in adulthood. This publication considers potential markers of the so-called fast life strategy — a life cycle characterized by a high disease risk, as well as the conditions leading to the formation of such a strategy. In the future, they may allow stratifying groups at high risk of premature death from cardiovascular and metabolic diseases in routine clinical practice and conducting their early prevention.